The economics of high rates of fertilizer on South Taranaki dairy farms : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Massey University of Manawatu - Graham, John Victor (Massey University, 1964)
This thesis reports the findings of a survey conducted to test the hypothesis that the use of increased rates of stock and fertilizer could lead to increased production on dairy farms in South Taranaki. Increases in stocking rates and fertilizer rates had been taking place on some farms in the South Taranaki area for several seasons preceding the 1961-62 season. Farmers making these increases suggested that other management changes were necessary when increased rates of stock and fertilizer were used. These changes, when taken together, were thought to lead to increases in production. Thus the specific aim of the survey was to find a well proven management system incorporating increased rates of stock and fertilizer, and to evaluate this system in physical and financial terms. No attempt was made to find the best management system for increasing production since this attempt would have been defeated by the important differences between farms and between farmers. Rather, the aim was to fully document one management system so that the uncertainty associated with its adoption by farmers would be reduced. Should farmers feel that there are management systems superior to the one evaluated in this study, then it is to be hoped that a demand for further research will arise. [From Introduction]
Keywords: New Zealand Taranaki; Economic aspects; Dairy farming; Fertilizers